Modeling of psychiatric disorders using induced pluripotent stem cell-related technologies - Takanobu Nakazawa; Ryota Hashimoto; Kazuhiro Takuma; Hitoshi Hashimoto (Elsevier, 2019)
Since induced pluripotent stem cells (iPSCs) were generated from mice and humans by Professor Shinya Yamanaka et al. in 2006 and 2007, respectively, a variety of human-derived cells have been generated, including myocardial, liver, retinal pigment epithelial, and neuronal cells. These iPSCs are now used not only in clinical research focusing on regeneration and transplantation in diverse medical fields, but also in molecular and cellular pathological studies. Importantly, by using human-derived iPSCs, it has become possible to conduct drug discovery research that more accurately models the pathology of human diseases. In research on psychiatric disorders, iPSC-related technologies, which have enabled the use of neuronal cells that carry the genetic information of the patients, will be important for elucidating not only the molecular and cellular etiology of psychiatric disorders but also the molecular mechanisms of drug action in these disorders. This review outlines the pharmacological research of psychiatric disorders that utilizes iPSC-related technologies. Keywords: Induced pluripotent stem cell (iPSC), Psychiatric disorders, Schizophrenia, Bipolar disorder, Autism spectrum disorder, Clozapine, Lithium